Adjuvant chemotherapy use and outcomes of patients with high‐risk versus low‐risk stage II colon cancer. Issue 4 (20th October 2014) - Kumar, Aalok; Kennecke, Hagen F.; Renouf, Daniel J.; Lim, Howard J.; Gill, Sharlene; Woods, Ryan; Speers, Caroline; Cheung, Winson Y.
<x xml:space="preserve">Abstract</x> BACKGROUND Adjuvant chemotherapy (AC) is frequently considered in patients with stage II colon cancer who are considered to be at high risk. However, to the authors' knowledge, the survival benefits associated with AC in these patients remain largely unproven. In the current study, the authors sought to examine the use of AC in patients with AJCC stage II colon cancer and to compare the impact of AC on outcomes in patients with high‐risk versus low‐risk disease in a population‐based setting. METHODS Patients with stage II colon cancer who were evaluated at 1 of 5 regional cancer centers in British Columbia from 1999 to 2008 were analyzed. Kaplan‐Meier and Cox regression methods were used to correlate high‐risk versus low‐risk status and receipt of AC with recurrence‐free survival (RFS), disease‐specific survival (DSS), and overall survival (OS). RESULTS A total of 1697 patients were identified: 1286 (76%) with high‐risk and 411 (24%) with low‐risk disease, among whom 373 (29%) and 51 (12%), respectively, received AC. Individuals with high‐risk disease treated with AC were younger (median age, 62 years vs 72 years; P<.001) and had better Eastern Cooperative Oncology Group performance status (0/1: 47% vs 33%; P = .001). For high‐risk patients, AC was associated with improved OS (hazard ratio [HR], 0.65; 95% confidence interval [95% CI], 0.50‐0.83 [P = .001]). However, no significant benefits with regard to RFS or DSS were observed. Subgroup analyses revealed that AC in patients with T4 disease was associated with significantly improved RFS (HR, 0.63; 95% CI, 0.42‐0.95 [P = .03]), DSS (HR, 0.59; 95% CI, 0.37‐0.93 [P = .02]), and OS (HR, 0.50; 95% CI, 0.33‐0.77 [P = .002]). For patients with low‐risk disease, AC was associated with inferior RFS (HR, 2.18; 95% CI, 1.00‐4.79 [P = .05]) and DSS (HR, 3.01; 95% CI, 1.10‐8.23 [P = .03]). CONCLUSIONS In this population‐based analysis, AC was associated with an OS advantage in high‐risk patients, most likely due to patient selection. RFS, DSS, and OS benefits were mainly observed in patients with T4 disease, suggesting a limited role for AC in patients deemed to be high risk by non‐T4 features. Cancer 2015;121:527–534. © 2014 American Cancer Society.